1995
DOI: 10.1891/0886-6708.10.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Using Couple Data to Determine Domestic Violence Rates: An Attempt to Replicate Previous Work

Abstract: Research methodology using only one spouse to report for the couple has been questioned. Szinovacz (1983) reported higher rates of violence when both spouses responded to six items on Straus’s Conflict Tactics Scale (CTS). The purpose of this study was to replicate her methodology by using all items measuring severe violence in the latest CTS scale with 94 military couples, to see if couple reports of violence indicated higher rates of violence compared to individual spouses’ reports. Results were similar to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…All data were obtained by self-report, which is subject to reduced reliability and re-call bias (Johnson & Fendrich, 2005). Our use of audio computer-assisted self-interview (ACASI) techniques to collect data on partner violence may have reduced social desirability bias, but there may be systematic differences in the reliability of reporting partner violence by gender (Bohannon, Dosser, & Lindley, 1995; Reed, 2008). Several authors have suggested that men may be less willing than women to admit to being victims of intimate partner violence, and women may be more apt to identify themselves as perpetrators of violence (Caetano, Schafer, Field, & Nelson, 2002; Szinovacz & Egley, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…All data were obtained by self-report, which is subject to reduced reliability and re-call bias (Johnson & Fendrich, 2005). Our use of audio computer-assisted self-interview (ACASI) techniques to collect data on partner violence may have reduced social desirability bias, but there may be systematic differences in the reliability of reporting partner violence by gender (Bohannon, Dosser, & Lindley, 1995; Reed, 2008). Several authors have suggested that men may be less willing than women to admit to being victims of intimate partner violence, and women may be more apt to identify themselves as perpetrators of violence (Caetano, Schafer, Field, & Nelson, 2002; Szinovacz & Egley, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies, which may highlight perceptual and labeling differences between romantic partners, have empirical and clinical implications. For instance, Bohannon et al (1995) noted that it may be necessary for future researchers to examine dyadic responses when measuring subjective and/or sensitive relationship characteristics, such as victimization. Furthermore, because differences in defining courtship violence may affect the safety and emotional functioning of dating partners, increased educational programs may be needed to sensitize partners to the possibility of differing perceptions of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (e.g., Szinovacz, 1983;Szinovacz & Egley, 1995) examining domestic violence generally reveal discrepant findings between analyses utilizing individuals' reports and those using couple data. One such finding is that, when responses from both members of a couple are used, agreement between spouses tends to be poor regarding specific acts of violence (Bohannon, Dosser, & Lindley, 1995) and regarding the level of violence in the relationship (Langhinrichsen-Rohling & Vivian, 1994). This lack of concurrence may reflect differential reporting patterns between members of a couple.…”
Section: Review Of Domestic Violence Findings Using Couple Datamentioning
confidence: 99%
“…If a participant claimed to be a victim of sexual violence, the self-report was considered a case of sexual violence victimization, regardless of the spouse's confirmation. It should be noted, however, that some researchers in this field suggest relying upon both partners [18].…”
Section: Methodsmentioning
confidence: 99%